RNA-seq analysis reveals the effect of the metamorphic cue (juvenile oysters) on the Rapana venosa larvae - Yang, Mei-Jie; Shi, Ying; Lin, Zhi-Shu; Shi, Pu; Hu, Zhi; Zhou, Cong; Hu, Peng-Peng; Yu, Zheng-Lin; Zhang, Tao; Song, Hao (Frontiers in Marine Science, 2023)
As a vital developmental event, metamorphosis controls the population dynamics of most marine invertebrates and affects the breeding of economic shellfish. Rapana venosa is an economically important species in China, but artificial aquaculture has hampered its metamorphosis process. Previous studies have found that juvenile oysters can effectively induce the metamorphosis of R. venosa, but the specific induction mechanism is not clear. Here, we investigated the mechanism underlying the response of R. venosa to juvenile oysters through the RNA-seq analysis. In this study, the gene set responses to metamorphosis cues (juvenile oysters) in R. venosa were identified, and GO and KEGG enrichment analyses were further performed on these gene sets. The results showed that the expression of the prototype of the class of immediate early genes, the transcription factor AP-1, was rapidly and significantly increased, and the molecular chaperone of NOS, HSP90, exhibited lower expression in the M12 group than in the control group. In contrast, the expression of inhibitors of apoptosis (IAPs) was significantly increased upon exposure to juvenile oysters. Additionally, the Wnt signaling pathway and MAPK signaling pathway were enriched in the trend analysis. These pathways may also play critical regulatory roles in the response to juvenile oysters. Taken together, the results show that competent larvae rapidly respond to the inducing effects of oysters via some immediate early genes, such as the transcription factor AP-1, which may further regulate downstream pathways such as the MAPK signaling pathway to cause subsequent changes, including a decrease in HSP90 and an increase in IAPs. These changes together may regulate the metamorphosis of R. venosa. This study provides further evidence that juvenile oysters are the metamorphosis cues of R. venosa, which may enhance our understanding of the metamorphosis mechanism in this marine invertebrate.